2-Triazole-Substituted Adenosines: A New Class of Selective A(3) Adenosine Receptor Agonists, Partial Agonists, and Antagonists - Cosyn, Liesbet (J Med Chem, 2006)
“Click chemistry” was explored to synthesize two series of 2-(1,2,3-triazolyl)adenosine derivatives (1–14). Binding affinity at the human A(1), A(2A), and A(3)ARs (adenosine receptors) and relative efficacy at the A(3)AR were determined. Some triazol-1-yl analogues showed A(3)AR affinity in the low nanomolar range, a high ratio of A(3)/A(2A) selectivity, and a moderate-to-high A(3)/A(1) ratio. The 1,2,3-triazol-4-yl regiomers typically showed decreased A(3)AR affinity. Sterically demanding groups at the adenine C2 position tended to reduce relative A(3)AR efficacy. Thus, several 5′-OH derivatives appeared to be selective A(3)AR antagonists, i.e., 10, with 260-fold binding selectivity in comparison to the A(1)AR and displaying a characteristic docking mode in an A(3)AR model. The corresponding 5′-ethyluronamide analogues generally showed increased A(3)AR affinity and behaved as full agonists, i.e., 17, with 910-fold A(3)/A(1) selectivity. Thus, N(6)-substituted 2-(1,2,3-triazolyl)-adenosine analogues constitute a novel class of highly potent and selective nucleoside-based A(3)AR antagonists, partial agonists, and agonists.